2000
DOI: 10.1200/jco.2000.18.13.2593
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Thalidomide in AIDS-Related Kaposi’s Sarcoma

Abstract: Oral thalidomide was tolerated in this population at doses up to 1,000 mg/d for as long as 12 months and was found to induce clinically meaningful anti-KS responses in a sizable subset of the patients. Additional studies of this agent in KS are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(113 citation statements)
references
References 55 publications
1
110
0
2
Order By: Relevance
“…Indeed clinical trials utilizing two such agents (TNP 470 and thalidomide) are currently ongoing (6,8,9). Recently, lead compounds based on a strategy that aims to cause direct damage to the tumor endothelium resulting in rapid and catastrophic shutdown in the vascular function of the tumor and leading to extensive secondary tumor cell death (11) also have entered clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed clinical trials utilizing two such agents (TNP 470 and thalidomide) are currently ongoing (6,8,9). Recently, lead compounds based on a strategy that aims to cause direct damage to the tumor endothelium resulting in rapid and catastrophic shutdown in the vascular function of the tumor and leading to extensive secondary tumor cell death (11) also have entered clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This was based on evidence that thalidomide could inhibit angiogenesis, block tumor necrosis factor alpha (TNF-a), and inhibit intercellular adhesion molecules and basement membrane formation (7). Preliminary results from two Phase II clinical trials showed that there was activity of thalidomide in a 99 subset of patients with KS (8,9). Based on the encouraging results observed with thalidomide and TNP-470, clinical research into the antiangiogenic activities of these and other agents, including interleukin-12 and angiostatin, continues (3,7).…”
mentioning
confidence: 99%
“…Moreover, in the early 1990s, thalidomide was shown to ameliorate symptoms associated with the wasting syndrome of AIDS (3). Today, thalidomide is in clinical trials for HIV ulcers and wasting (3 -6), Crohn's disease (7), rheumatoid arthritis (8,9), chronic host-versus-graft disease (10), Behcet's vasculitis (11), and cancer, including multiple myeloma (12 -15), AIDS Kaposi's sarcoma (16), and other solid tumors (17 -20).…”
Section: Introductionmentioning
confidence: 99%
“…8 Several clinical studies indicate that thalidomide may possess antineoplastic properties in myeloma, 9 melanoma, 10 hormonerefractory prostate carcinoma, 11 high-grade glioma, and Kaposi sarcoma. 12 Several considerations support the potential use of thalidomide in patients with HCC. First, HCC is a very vascular tumor, and it has been demonstrated that angiogenesis is an essential element of tumor progression and metastatic proliferation; 13 thalidomide, as discussed above, is an antiangiogenic agent.…”
mentioning
confidence: 99%